1983
DOI: 10.1177/000169938302600102
|View full text |Cite
|
Sign up to set email alerts
|

The Uses of Alcohol and Their Cultural Regulation

Abstract: Alcoholic beverages have multiple objective uses that can be analyzed to some degree independently of prevailing cultural attitudes. Three main uses which are directly based on the physical properties of beverage alcohol as a substance are identified: nutritional use. medicinal use and use as an intoxicant The following physical properties of beverage alcohol are singled out for discussion. medicinal effects, caloric content, liquid state, taste and intoxicating effects. The use of alcohol as a gift and for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 4 publications
0
21
0
2
Order By: Relevance
“…The stand-up bar of the English pub, with drinkers standing in a line. Mäkelä (1983) Two basic types of cultural configurations related to how alcohol is used: 1. Nutritional use of alcohol (e.g.…”
Section: The Typological Traditionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stand-up bar of the English pub, with drinkers standing in a line. Mäkelä (1983) Two basic types of cultural configurations related to how alcohol is used: 1. Nutritional use of alcohol (e.g.…”
Section: The Typological Traditionmentioning
confidence: 99%
“…Until Mäkelä's discussion of ''the uses of alcohol and their cultural regulation'' (1983), there had been little consideration of the different uses of alcohol and meanings attributed to it as a feature of drinking cultures. Mäkelä (1983) suggested that a defining feature of drinking cultures is how alcohol is used, arguing that in some cultures alcohol is used predominantly for nutrition (e.g. Italy) and in other cultures as an intoxicant (e.g.…”
Section: The Typological Traditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Par ailleurs, plusieurs auteurs appuient l'idée de la possibilité d'une coexistence de pratiques de consommation d'alcool dans une même société, illustrant une variabilité d'attitudes et de symbolisations en matière d'alcool entre les groupes sociaux (Mäkelä, 1983 ;Levine, 1992 ;Room et Mäkelä, 2000). Les travaux en psychosociologie ont toutefois une limite importante de généralisation des résul-tats, puisqu'ils s'appuient la plupart du temps, comme ceux de Bales (1946), sur des données ethnographiques ou de groupes sociaux non représentatifs à l'ensemble des types de sociétés, ou des sociétés modernes (Room, 1988).…”
Section: Contributions Et Limites De L'approche Socioculturelleunclassified